EFEKTIVITAS MODEL TEAMS GAMES TOURNAMENT (TGT) DAN GAMES BASED LEARNING (GBL) BERBASIS ICE BREAKING TERHADAP RASA PERCAYA DIRI PESERTA DIDIK DI SEKOLAH DASAR - Agustina, Meliana; Taufik, M.; Rahmani, Anggi (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to: (1) determine the effectiveness of the Teams Games Tournament (TGT) and Game-Based Learning (GBL) models based on ice breaking in enhancing elementary students’ self-confidence; and (2) examine whether there is a significant difference in effectiveness between the TGT and GBL models. The study employed an experimental method with a quasi-experimental design. The research subjects were 50 fourth-grade students (class 4A) at SDN Serang 11. Data were collected using questionnaires and documentation, and the instruments were tested for validity and reliability. Data analysis was conducted using Microsoft Excel through: (1) descriptive analysis (mean, median, and mode), (2) prerequisite tests (normality and homogeneity), and (3) hypothesis testing using a parametric independent samples t-test. The results showed that the average posttest score of class A was 76.34, while class B scored 73.25. Thus, regarding the first hypothesis, the TGT model was more effective in improving students’ self-confidence. For the second hypothesis, the independent samples t-test yielded a significance value indicating a difference in effectiveness between the TGT and GBL models. In conclusion, there is a significant difference in effectiveness between TGT and GBL based on ice breaking in enhancing elementary students’ self-confidence.